The business analyst's handbook - Podeswa, Howard (Australia ; Boston, Mass. : Course Technology PTR : A part of Cengage Learning, 2009)
Provides a useful compendium of tools, tables, lists, and templates that BAs can use on-the-job to carry out their tasks.
Includes bibliographical references and index.
oif 12/06/15
Loan
Keywords: Systems Analysis; Task Performance and Analysis; Business analysts; Business planning; Business requirements analysis; Business -- Computer network resources